2014
DOI: 10.5688/ajpe78476
|View full text |Cite
|
Sign up to set email alerts
|

Online Virtual-Patient Cases Versus Traditional Problem-Based Learning in Advanced Pharmacy Practice Experiences

Abstract: Objective. To evaluate the efficacy of faculty-led problem-based learning (PBL) vs online simulatedpatient case in fourth-year (P4) pharmacy students. Design. Fourth-year pharmacy students were randomly assigned to participate in either online branchedcase learning using a virtual simulation platform or a small-group discussion. Preexperience and postexperience student assessments and a survey instrument were completed. Evaluation. While there were no significant differences in the preexperience test scores be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
93
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(95 citation statements)
references
References 14 publications
1
93
0
1
Order By: Relevance
“…They found no difference in quiz scores between the two groups of students, but online learners were significantly less satisfied with the course and instructor overall. Al‐Dahir, Bryant, Kennedy, and Robinson () found that fourth‐year pharmacy students had better post learning outcomes in a faculty‐led problem‐based learning course than did online students. Mosalanejad, Shahsavari, Sobhnian, and Dastpak () found that first‐year nursing students performed better on a theoretical examination in an online course format, but that there were no significant differences in performance for a structured clinical exam.…”
Section: Online Versus Face‐to‐face Learning Outcomesmentioning
confidence: 99%
“…They found no difference in quiz scores between the two groups of students, but online learners were significantly less satisfied with the course and instructor overall. Al‐Dahir, Bryant, Kennedy, and Robinson () found that fourth‐year pharmacy students had better post learning outcomes in a faculty‐led problem‐based learning course than did online students. Mosalanejad, Shahsavari, Sobhnian, and Dastpak () found that first‐year nursing students performed better on a theoretical examination in an online course format, but that there were no significant differences in performance for a structured clinical exam.…”
Section: Online Versus Face‐to‐face Learning Outcomesmentioning
confidence: 99%
“…In addition to online modules, online virtual patients are used in educating health professionals, 21,22 with increased use in pharmacy education over the last decade. [23][24][25][26][27][28][29][30][31] Virtual patient programs allow learners to gain experience by making and learning from decisions in a safe environment, 25 thus supporting the active experimentation stage of experiential learning theory. 32 The inclusion of "scenario-based" virtual patient programs can be effective where strategic, rather than procedural, learning goals are required.…”
Section: Introductionmentioning
confidence: 99%
“…Contrairement à ce qui est attendu dans d'autres dispositifs, il n'y avait ici généralement pas de bonne ou de mauvaise réponse [17]. Les niveaux d'aisance plutôt bas ne sont pas le reflet d'un manque de connaissances.…”
Section: Discussionunclassified